Floating on a Malayan breeze : travels in Malaysia and Singapore - Vadaketh, Sudhir Thomas (NUS Press ; Hong Kong University Press, 2012)
"What happens after a country splits apart? Forty-seven years ago Singapore separated from Malaysia. Since then, the two countries have developed along their own paths. Malaysia has given preference to the majority Malay Muslims -- the bumiputera, or sons of the soil. Singapore, meanwhile, has tried to build a meritocracy -- ostensibly colour-blind, yet more encouraging perhaps to some Singaporeans than to others. How have these policies affected ordinary people? How do these two divergent nations now see each other and the world around them? Seeking answers to these questions, two Singaporeans set off to cycle around Peninsular Malaysia, armed with a tent, two pairs of clothes and a daily budget of three US dollars each. They spent 30 days on the road, cycling through every Malaysian state, and chatting with hundreds of Malaysians"--Publisher's description.